AI Enabled Cloud Computing Pipeline: Architectural Framework, Challenges and Future Directions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Cloud computing has converted the landscape of cutting-edge IT infrastructure, presenting scalability and costefficiency. Simultaneously, synthetic intelligence (AI) has developed to enable machines to carry out duties that require humanlike intelligence. This studies paper explores the intersection of AI and cloud computing, focusing at the architectural framework of AI-enabled cloud computing pipelines. These pipelines encompass crucial levels along with statistics ingestion, preprocessing, version schooling, deployment, and tracking. Challenges on this area, along with records privacy, protection, scalability, equity, and ethics, are discussed. The paper also highlights rising tendencies, including side AI, quantum computing, stronger AI explain ability, and regulatory improvements. By addressing those challenges and embracing emerging developments, organizations can harness the overall ability of AI-enabled cloud computing pipelines, permitting informationpushed choice-making and transformative programs throughout industries.